Simulasi Fluktuasi Temperatur pada Wind Tunnel Transien Jenis Gun Tunnel - Widodo, Agung Sugeng (Jurnal Rekayasa Mesin, 2014)
Wind tunnels can be used to simulate supersonic and hypersonic flight conditions, but different wind tunnels can give different results for the same model and nominal flow conditions. Short duration wind tunnels gun tunnels rely on a transient compression process and are likely to generate significant turbulent fluctuations in the nozzle reservoir region. In the present study, a simulation to predict stagnation temperature fluctuation was conducted into transient wind tunnel gun tunnel by adopting a method of other worker. The friction velocity Reynolds numbers for the gun tunnel considered presently were Re ï´ = 31,579. The RMS stagnation temperature fluctuations, when averaged over the pipe flow diameter, are estimated to be 15.3. The estimated RMS value in the case of the gun tunnel is significantly larger than the experimental value previously measured on the centre line of the gun tunnel nozzle of 2.3 K. The difference observed between the inferred and measured temperature fluctuations in the gun tunnel case may be related to spatial variations in the temperature fluctuations. The present approach for estimating the magnitude temperature fluctuations should be refined, but more detailed measurements of temperature fluctuations in such facilities are also required.Keywords: Temperature Fluctuations, Combustion, Gun Tunnel, Shock Tunnel